2020
DOI: 10.7554/elife.54916
|View full text |Cite
|
Sign up to set email alerts
|

Control of Slc7a5 sensitivity by the voltage-sensing domain of Kv1 channels

Abstract: Many voltage-dependent ion channels are regulated by accessory proteins. We recently reported powerful regulation of Kv1.2 potassium channels by the amino acid transporter Slc7a5. In this study, we report that Kv1.1 channels are also regulated by Slc7a5, albeit with different functional outcomes. In heterologous expression systems, Kv1.1 exhibits prominent current enhancement ('disinhibition') with holding potentials more negative than −120 mV. Knockdown of endogenous Slc7a5 leads to larger Kv1.1 currents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…A recent investigation identified a unique functional interaction between the Kv channels, Kvβ, and SLC7a5, a neutral amino acid transporter. Lamothe et al demonstrated a profound alteration in the expression and function of Kv1.2 when co-expressed with Kvβ and SLC7a5 [30]. In the present study, we identified that the deletion of Kvβ2 led to a decreased expression of SLC41a3, which is a distinct member of the magnesium solute carrier transport family (SLC41) and, therefore, further evaluated the magnesium effects in the Kvβ2 knockout hearts.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A recent investigation identified a unique functional interaction between the Kv channels, Kvβ, and SLC7a5, a neutral amino acid transporter. Lamothe et al demonstrated a profound alteration in the expression and function of Kv1.2 when co-expressed with Kvβ and SLC7a5 [30]. In the present study, we identified that the deletion of Kvβ2 led to a decreased expression of SLC41a3, which is a distinct member of the magnesium solute carrier transport family (SLC41) and, therefore, further evaluated the magnesium effects in the Kvβ2 knockout hearts.…”
Section: Discussionmentioning
confidence: 52%
“…Hearts were stabilized for 10 min, and MAP data were acquired using the 8-channel PowerLab system (AD Instruments, Sydney, Australia). Programmed electrical stimulation was performed as described previously [29,30]. Briefly, excised hearts were perfused with the Krebs-Hanseleit buffer and stabilized for 10 min; after which, the baseline MAPs were recorded.…”
Section: Monophasic Action Potentialsmentioning
confidence: 99%
“…These are transported into the brain through the large neutral amino acids transporter (LAT1, coded by the SLC7A5 gene), responsible for the transport tryptophan and other amino acids such as BCAAs or threonine. Besides amino acids transport, LAT1 has been reported to regulate Kv1.2 potassium channels, 57 modifying the functional outcomes of epilepsy‐linked channelopathies 58 . On top of that, mutations SLC7A5 (together with other variants in genes encoding for large amino acid transporters) increase the risk of autism spectrum disorder 59,60 and is essential for perinatal neuronal excitability 61 and survival and granule cell development through mTOR regulation 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Others found that Drosophila KCNQ forms complexes with the nontransporting Drosophila SMIT2 ortholog cupcake (dSLC5A11) (242) and that mammalian KCNQ2/3 forms complexes with the sodiumcoupled neurotransmitter transporters DAT and GLT1 (243,244). Also, Kv1.2 (KCNA2) forms complexes with LAT1 (SLC7A5), a neutral amino acid transporter (245)(246)(247).…”
Section: Future Of the Fieldmentioning
confidence: 99%